1958
DOI: 10.2475/ajs.256.6.384
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene sequence in southeastern part of the Puget Sound lowland, Washington

Abstract: Sound lowland has resulted in a refinement and expansion of the sequence originally described by Willis in 1898. Willis' t1equence of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 5 publications
0
16
1
Order By: Relevance
“…The valleys were then modified by the Vashon glacier and were drowned by submergence. Hansen and Mackin (1949), Sceva (1957), and Crandell, Mullineaux, and Waldron (1958) confirmed that the valleys were cut into an overall fill, but they showed that the fill consisted of deposits of several different glacial and nonglacial episodes. No evidence was found to negate Bretz' hypothesis of pre-Vashon origin by fluvial erosion caused by uplift, and of only modification of the valleys by the Vashon glacier.…”
Section: Origin Of Duwamish Valley and Adjacent Drift Plainmentioning
confidence: 90%
“…The valleys were then modified by the Vashon glacier and were drowned by submergence. Hansen and Mackin (1949), Sceva (1957), and Crandell, Mullineaux, and Waldron (1958) confirmed that the valleys were cut into an overall fill, but they showed that the fill consisted of deposits of several different glacial and nonglacial episodes. No evidence was found to negate Bretz' hypothesis of pre-Vashon origin by fluvial erosion caused by uplift, and of only modification of the valleys by the Vashon glacier.…”
Section: Origin Of Duwamish Valley and Adjacent Drift Plainmentioning
confidence: 90%
“…The Sherwin till in California (Blackwelder, 1931) underlies the Bishop ash bed at its type locality (Sharp, 1968), so it must also be of this age, while the Dyer till in the White Mountains has also been dated at c. 1.0a (Elliot-Fish, 1987). The Salmon Springs drift of Washington State (Crandell et al, 1958) is interbedded with the Lake Tapps tepha dated at 0.8-0.9 Ma (VTlestgate et al, 1987), and is probably Nebraskan in age. The till buried by lava dated at 0.7 Ma in the Mt Garibaldi volcanic belt (Green et al, 1988) is probably of this age.…”
Section: The Quaternary Cold Eventsmentioning
confidence: 98%
“…The chronology of the advance and retreat of the Late Wisconsinan Fraser Glaciation in the Puget Lowland has been worked out over the past several decades (Armstrong et al, 1965;Crandell et al, 1958;Blunt et al, 1987;Easterbrook, 1963Easterbrook, ,1969Easterbrook, ,1986Easterbrook ef a/., 1981Easterbrook ef a/., ,1988Mullineauxef al., 1965;Westgate et al, 1987), and now comprises one of the best-dated, long-record, Pleistocene sequences in the world. However, papers published during the same time period on interpretations of specific depositional environments of some of the sediments have not always been in accord with one another.…”
Section: Introductionmentioning
confidence: 99%